2015
DOI: 10.1007/s00253-015-7052-9
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanisms and microbial structure of partial denitrification with high nitrite accumulation

Abstract: Nitrite (NO2 (-)-N) accumulation in denitrification can provide the substrate for anammox, an efficient and cost-saving process for nitrogen removal from wastewater. This batch-mode study aimed at achieving high NO2 (-)-N accumulation over long-term operation with the acetate as sole organic carbon source and elucidating the mechanisms of NO2 (-)-N accumulation. The results showed that the specific nitrate (NO3 (-)-N) reduction rate (59.61 mg N VSS(-1) h(-1) at NO3 (-)-N of 20 mg/L) was much higher than specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(75 citation statements)
references
References 34 publications
7
65
3
Order By: Relevance
“…The latter might have been related to the seed sludge for denitrifiers used during both experiments. The high PdN results using acetate and glycerol were consistent with other studies where nitrite accumulation as indicator of PdN has been reported (Baideme et al., ; Bill et al., ; Du et al., ; Ge et al., ; Gong et al., ; Park, Brotto, van Loosdrecht, & Chandran, ; Sharp, Niemiec, Khunjar, Galst, & Deur, ; Uprety, ; van Rijn et al., ; Yang, Wang, & Zhou, ).During the batch experiments, sludge under low carbon loading (from wastewater) was used without acclimation to any of the carbon sources tested while for the long‐term testing methanol acclimated sludge was used. Previous work by Cao et al.…”
Section: Discussionsupporting
confidence: 90%
“…The latter might have been related to the seed sludge for denitrifiers used during both experiments. The high PdN results using acetate and glycerol were consistent with other studies where nitrite accumulation as indicator of PdN has been reported (Baideme et al., ; Bill et al., ; Du et al., ; Ge et al., ; Gong et al., ; Park, Brotto, van Loosdrecht, & Chandran, ; Sharp, Niemiec, Khunjar, Galst, & Deur, ; Uprety, ; van Rijn et al., ; Yang, Wang, & Zhou, ).During the batch experiments, sludge under low carbon loading (from wastewater) was used without acclimation to any of the carbon sources tested while for the long‐term testing methanol acclimated sludge was used. Previous work by Cao et al.…”
Section: Discussionsupporting
confidence: 90%
“…While the AnAOB process is easily controlled whenever nitrite is available, PdN selection has become a critical step determining success of the PdN‐AnAOB approach (Kumar & Lin, ). Nitrite accumulation as indicator of PdN has been reported in many studies when fast carbon sources such as acetate (Du et al, ; Ge et al, ; Gong et al, ; Le et al, ; Van Rijn, Tal, & Barak, ; Yang, Wang, & Zhou, ) or glycerol (Baideme et al, ; Bill et al, ; Park, Brotto, Loosdrecht, & Chandran, ; Sharp et al, ; Uprety, ) were used for denitrification. Furthermore, other research also showed that COD/N ratio, pH, DO level, and SRT could be important factors impacting PdN performance (Almeida, Júlio, Reis, & Carrondo, ; Beccari, Passino, Ramadori, & Tandoi, ; Glass & Silverstein, ; Obaja, MacÉ, & Mata‐Alvarez, ).…”
Section: Introductionmentioning
confidence: 99%
“…The type of carbon source can significantly influence the NO 2 --N accumulation performance. It could be attributed by diverse organics affected the selection and enrichment of NO 2 --N-accumulating bacteria [24], and the discrepency of NO 3 --N and NO 2 --N reduction rates would also emerge [7,25]. Previous literatures have evidenced that simple micromolecule organic materials could easily harvest NO 2 --N accumulating organisms compared with complex carbon source.…”
Section: Carbon Sourcesmentioning
confidence: 99%